COMBATING THE SILENT THREAT OF STREET TRADING RESULTING IN ILLEGAL DUMPING OF WASTE IN UGANDA - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Obieshi, Eregbuonye; Akinsulore, Adedoyin Olusegun; Owuche, Antai Godswill; Kolawole, Adebayo Adesoji (Universitas Syiah Kuala, 2024)
The Uganda government has taken legal and institutional measures (such as the Uganda constitution, National Environmental Act and the Climate Change Act) to ensure clean and healthy environment and resolving major environmental issues. However, the rate of street trading within the terrain of Uganda, has resulted in the illegal dumping of refuse. It suffices to state that illegal dumping of refuse could generate major environmental issues such as flood, soil pollution, water pollution, air pollution, and destruction of habitat. This study embarks on a hybrid method of study in examining the need to combat the threat of street trading associated with the illegal dumping of waste. 290 questionnaires were sent to respondents residing in the various regions of Uganda. The data obtained through the questionnaire was analyzed using a descriptive and analytical method of research. The study therefore found that, there are unchecked incidents of street trading which often result in illegal dumping of refuse. Furthermore, the continuous dumping of refuse as a result of street trading could result in severe environmental pollution. The study therefore concludes and recommends that for a sustainable environment free from any form of pollution, there is a need for the Uganda government to through institutional measures reinforce the laws against illegal dumping of refuse resulting from street trading.